Low efficiency roll-off and high performance OLEDs employing alkyl group modified iridium(iii) complexes as emitters. Issue 112 (24th November 2016) - Wen, Li-Li; Yu, Jing; Sun, Hai-Zhu; Shan, Guo-Gang; Xie, Wen-Fa; Su, Zhong-Min
Abstract : Four Ir(iii ) dyes employing modified 1, 2-diphenyl-1 H -benzoimidazole ligands were synthesized. Doped device using t Bu-Ir-PI with tert -butyl group as emitter achieves high η c of 42.0 cd A −1 and η p of 27.0 lm W −1, respectively. Abstract : Significant efficiency roll-off of phosphorescent organic light-emitting diodes (PHOLEDs) is a long-standing issue that limits their wider application. To address this problem, four iridium(iii ) complexes modified by methyl or tert -butyl groups were designed and synthesized, denoted asMe-Ir-PI, t Bu-Ir-PI, Me-Ir-PB, and t Bu-Ir-PB . Their photophysical, electrochemical, and electroluminescent properties were studied in detail. The electroluminescent performances of devices based on t Bu-Ir-PI and t Bu-Ir-PB were better than those based onMe-Ir-PI andMe-Ir-PB . The best performance was achieved by the doped device employing t Bu-Ir-PI as the emitter with maximum current efficiency of 42.0 cd A −1 and maximum power efficiency of 27.0 lm W −1 . Even at a practical brightness of 1000 cd m −2, the current efficiency and power efficiency remained as high as 39.2 cd A −1 and 22.3 lm W −1 . Notably, all doped devices exhibited low efficiency roll-off, especially for device incorporation of t Bu-Ir-PB as the guest emitter, which had extremely low roll-off of 0.9%. Meanwhile, non-doped devices based on these iridium(iii ) complexes also displayed good EL performances.